Two‐Line Elements Based Thermospheric Mass Density Specification From Parameter Optimization of a Physics‐Based Model - Dexin Ren; Jiuhou Lei (Space Weather)
Abstract Accurately estimating the mass density of the thermosphere can assist satellite operators in planning missions and optimizing satellite orbits, reducing the risk of collisions. The newly developed GOFT (Global Observation‐based Forecast for the Thermosphere) model specifies thermospheric mass density by optimizing uncertainty parameters in a physics‐based model based on model errors. This study extends the model to specify thermospheric mass density based on Two‐Line Elements (TLEs) from numerous space objects. The resulting mass density is validated against accelerometer‐derived mass density from different satellites. The comparison results revealed that assimilating TLEs into the GOFT model significantly improved the accuracy of the thermospheric mass density. In addition, the GOFT model also improved the accuracy of the electron density in the ionosphere, indicating that the assimilation capability of GOFT allows simultaneous specification of coupled ionosphere and thermosphere in future applications.